Analisis Perkembangan Ekspor Impor Barang Ekonomi di Provinsi Sumatera Utara - Sari Wulandari; Anggia Sari Lubis (Jurnal Administrasi Bisnis, 2019)
This study aims to determine the development of exports and imports of North Sumatra Province through export and import value indicators, balance sheets and trade ratios. Data analysis techniques in research are qualitative descriptive data analysis. The data sources in this study are secondary data downloaded through www.bps.go.id, especially data on exports and imports and the trade balance of economic goods groups in North Sumatra Province. The results showed that there was an increase and improvement that could be seen from the increase in the volume and value of exports of economic goods groups, a decrease in the volume and value of imports of economic goods groups as well as an increase in foreign trade ratios and a trade balance that showed positive foreign economic goods group controlled by exports.